Identifikasi Jenis - Jenis Tumbuhan Obat Tradisional Oleh Masyarakat Kawasan Hutan Lindung Meler Kuwus (Studi Kasus Desa Banteng Suru Kecamatan Kuwus Kabupaten Manggarai Barat Provinsi Nusa Tenggara Timur - Danggur, Yakobus Emilianus; Seran, Wilhelmina; Riwu Kaho, Norman P. L. B. (Wana Lestari, 2022)
Benteng Suru, located around Meler Kuwus Protected Forest Area reaches 30 ha out of a total village area of 273,2 ha. The people of this village area still bound by their ancestral heritage and one of them is the use of plants as traditional medicines to cure various diseases. The study aimed to determine the distribution of medical plants, utilization and conservation status of medical plants in the Meler Kuwus protection forest area, Benteng Suru village, West Manggarai regency. This research was conducted from October - December consists interviews, and exploring methods. This study found 28 species medical plants from 20 families, Asteraceae, Rutacea, Melastomaceae, Cyparaceae, Pittosporaceae, Ulmaceae, Zingiberaceae, Apiaceae, Pandanaceae, Buseraceae, Polypodiceae, Euphorbiaceae, Moraceae, Apocynaceae, Lauraceae, Verbenaceae, Poaceae, Mimisaceae, Piperaceae. The spatial distribution of medicinal plants grows in the altitude of 750- 100 m.a.s.l to 1000 - 1250 m.a.s.l and slope level starts from slightly flat, slightly slope, steep, and extremely steep areas. The most widely used medicinal plant part was the leaf (41%), while the lowest part used was the stem with the percentage of 5%. According to the IUCN, there are 3 categories of conservation of medicinal plants, namely Not Evaluated (NE) 68%, Least Concern (CL), 29% and Data Deficient (DD) 4%. While in the other hand, the conservation status of medicinal plants according to the Minister of Environment and Forestry Regulation No. P 20 of 2018 shows that 100% of the medicinal plants species that was found were included in the unprotected categories.